2014
DOI: 10.1002/jnr.23502
|View full text |Cite
|
Sign up to set email alerts
|

Multiassay analysis of the toxic potential of hydrogen peroxide on cultured neurons

Abstract: To clarify discrepancies in the literature on the adverse effects of hydrogen peroxide on neurons, this study investigated the application of this peroxide to cultured cerebellar granule neurons with six assays frequently used to test for viability. Cultured neurons efficiently cleared exogenous H2O2. Although viability was not affected by exposure to 10 µM hydrogen peroxide, an exposure to the peroxide in higher concentrations rapidly lowered, within 15 min, the cellular 3-(4,5-dimethylthiazol-2-yl)-2,5-diphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 61 publications
0
2
1
Order By: Relevance
“…It is well known that H 2 O 2 as a medical disinfectant is used in much higher concentrations (3% vol., i.e., 0.98 M). H 2 O 2 is also often considered as the key antibacterial or antitumor agent of PAW in synergy with other RONS [61]. However, in our studied maximum concentration of 10 mM H 2 O 2 diluted in DW, we did not observe any antibacterial effect (Figure 6) by H 2 O 2 itself, nor H 2 O 2 combined with PEF.…”
Section: Pef Only and H 2 O 2 Onlycontrasting
confidence: 67%
“…It is well known that H 2 O 2 as a medical disinfectant is used in much higher concentrations (3% vol., i.e., 0.98 M). H 2 O 2 is also often considered as the key antibacterial or antitumor agent of PAW in synergy with other RONS [61]. However, in our studied maximum concentration of 10 mM H 2 O 2 diluted in DW, we did not observe any antibacterial effect (Figure 6) by H 2 O 2 itself, nor H 2 O 2 combined with PEF.…”
Section: Pef Only and H 2 O 2 Onlycontrasting
confidence: 67%
“…H 2 O 2 clearance results primarily from catalase activity and the glutathione system and exhibits characteristic times ranging from 0.1 s to minutes. Nevertheless, the slower removal rates of H 2 O 2 can lead to not only higher sensor signals in vivo than expected from calibrations in vitro (as mentioned above), but also to a moderate accumulation of H 2 O 2 in the brain in the vicinity of the sensor. However, this H 2 O 2 accumulation is not expected to show any toxic effects unless it well exceeds 10 μM . For moderate rates of H 2 O 2 clearance (5 s –1 ), the highest accumulation of H 2 O 2 for the simulated sensor responses shown in Figure is 10 μM (faster and slower expected clearance rates result in peak concentrations of 7.25 and 13.5 μM, respectively) for Glut release at 1 μm, and in all cases, this value drops by ∼60% or more for release 3 μm or greater from the sensor surface.…”
Section: Resultsmentioning
confidence: 86%
“…However, this H 2 O 2 accumulation is not expected to show any toxic effects unless it well exceeds 10 μM. 26 For moderate rates of H 2 O 2 clearance (5 s −1 ), the highest accumulation of H 2 O 2 for the simulated sensor responses shown in Figure 2 is 10 μM (faster and slower expected clearance rates result in peak concentrations of 7.25 and 13.5 μM, respectively) for Glut release at 1 μm, and in all cases, this value drops by ∼60% or more for release 3 μm or greater from the sensor surface. The sensor response scales with H 2 O 2 concentration at the electrode surface, which can be elevated for Glut release events closest to the sensor surface that give rise to local H 2 O 2 accumulation.…”
Section: Model Development and Simulated Sensor Response To Glut Conc...mentioning
confidence: 92%
“…Previous studies revealed the 50% effective concentrations (EC 50 ) of hydrogen peroxide that caused toxicity (viability, cell death, or apoptosis) in mammalian cells: EC 50 values of 100 and 500 μM in mouse endothelial cell lines [39], <100 μM in rat neuronal B50 cells [40], 1 mM in human neuroblastoma SH-SY5Y cells [41], and 30-500 μM (depending on the exposure duration) in rat C6 glioma cells [42]. It has been reported that adverse effects in neurons were induced by 12−500 μM hydrogen peroxide [43], and 25−50 μM hydrogen peroxide led to apoptosis in human Jurkat T-lymphocytes [44]. Our reporter assays can detect 30−50 μM hydrogen peroxide at the lowest concentrations covering the EC 50 values mentioned above.…”
Section: Plos Onementioning
confidence: 99%